2020
DOI: 10.1002/cmdc.202000007
|View full text |Cite
|
Sign up to set email alerts
|

Early Drug‐Discovery Efforts towards the Identification of EP300/CBP Histone Acetyltransferase (HAT) Inhibitors

Abstract: EP300 and CBP (KAT3A/3B) are two highly homologous, multidomain, epigenetic coregulators that play central roles in transcription through the acetylation of lysine residues on histones and other proteins. Both enzymes have been implicated in human diseases, especially cancer. From a high‐throughput screen of 191 000 compounds searching for EP300/CBP histone acetyltransferase (HAT) inhibitors, 18 compounds were characterized by a suite of biochemical enzymatic assays and biophysical methods, including X‐ray cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A unifying aspect of EP300/CREBBP probes 1 – 3 is that they are all acetyl-CoA competitive. A competitive mechanism is unambiguously supported by kinetic studies of 1 and is inferred for 2 and 3 based on similarities in chemical structure, biochemical screening data, and overlap with the acetyl-CoA binding site in crystallographic studies . Due to this, their inhibition is expected to scale linearly with the amount of cofactor present in the enzyme reaction.…”
Section: Resultsmentioning
confidence: 99%
“…A unifying aspect of EP300/CREBBP probes 1 – 3 is that they are all acetyl-CoA competitive. A competitive mechanism is unambiguously supported by kinetic studies of 1 and is inferred for 2 and 3 based on similarities in chemical structure, biochemical screening data, and overlap with the acetyl-CoA binding site in crystallographic studies . Due to this, their inhibition is expected to scale linearly with the amount of cofactor present in the enzyme reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Further, their search led to the development of two compounds ( 18 , ) as Acetyl‐CoA competitive EP300/CBP HAT inhibitors with in vivo activity with IC50 values of 2.5 μM and 9 nM. (Huhn et al, 2020).…”
Section: Drugs Used For Epigenetic Therapymentioning
confidence: 99%
“…Further, their search led to the development of two compounds (18, ) as Acetyl-CoA competitive EP300/CBP HAT inhibitors with in vivo activity with IC50 values of 2.5 μM and 9 nM. (Huhn et al, 2020). | 691 inhibitor H 4 K 12 CoA (20) has shown a low K i value of 1.1 nM for HAT1, compare to both Acetyl-CoA and H4 peptide (Ngo et al, 2019) [Figure 5].…”
Section: Histoneacetyltransferasesmentioning
confidence: 99%
“…On the basis of A-485, Zhou et al identified a preclinical candidate B026 (5) with excellent pharmacological properties with the assistance of artificial intelligence and further optimization [26]. In the past decade, several other HAT inhibitors 6-8 with excellent potency have been reported [27][28][29][30][31]. A-485 represents a significant breakthrough, but the cell potency still requires improvement.…”
Section: Introductionmentioning
confidence: 99%